Noninvasive characterization of pancreatic tumor mouse models using magnetic resonance imaging. (7th April 2017) - Farr, Navid; Wang, Yak‐Nam; D'Andrea, Samantha; Gravelle, Kayla M; Hwang, Joo Ha; Lee, Donghoon
Abstract: The preclinical models of pancreatic adenocarcinoma provide an alternative means for determining the mechanisms of malignancy and possibilities for treatments, thus representing a resource of immense potential for cancer treatment in medicine. To evaluate different tumor models, quantifiable magnetic resonance imaging (MRI) techniques can play a significant role in identifying valuable in vivo biomarkers of tumor characteristics. We characterized three models of pancreatic cancer with multiparametric MRI techniques. Tumor stromal density of each tumor was measured using diffusion‐weighted imaging and magnetization transfer (MT‐MRI). Histologic measurement showed a similar trend with tumor fibrosis levels. Results indicated that MRI measurements can serve as a valuable tool in identifying and evaluating tumor characteristics. Abstract : We characterized three mouse models of pancreatic ductal adenocarcinoma with noninvasive multiparametric magnetic resonance imaging (MRI). Tumor cellularity and stromal density of each tumor were investigated using diffusion‐weighted MRI and magnetization transfer MRI, respectively. Histologic measurements showed a similar trend with tumor cellularity and fibrosis levels.